Non-destructive thermal wave method applied to study thermal properties of fast setting time endodontic cement - Picolloto, A. M.; Mariucci, V. V. G.; Szpak, W.; Medina, A. N.; Baesso, M. L.; Astrath, N. G. C.; Astrath, F. B. G.; Santos, A. D. [UNESP]; Moraes, J. C. S. [UNESP]; Bento, A. C. (American Institute of Physics (AIP), 2013)
The thermal wave method is applied for thermal properties measurement in fast endodontic cement (CER). This new formula is developed upon using Portland cement in gel and it was successfully tested in mice with good biocompatibility and stimulated mineralization. Recently, thermal expansion and setting time were measured, conferring to this material twice faster hardening than the well known Angelus Mineral trioxide aggregate (MTA) the feature of fast hardening (similar to 7 min) and with similar thermal expansion (similar to 12 mu strain/degrees C). Therefore, it is important the knowledge of thermal properties like thermal diffusivity, conductivity, effusivity in order to match thermally the tissue environment upon its application in filling cavities of teeth. Photothermal radiometry technique based on Xe illumination was applied in CER disks 600 mu m thick for heating, with prepared in four particle sizes (25, 38, 45, and 53) (mu) under barm, which were added microemulsion gel with variation volumes (140, 150, 160, and 170) mu l. The behavior of the thermal diffusivity CER disks shows linear decay for increase emulsion volume, and in contrast, thermal diffusivity increases with particles sizes. Aiming to compare to MTA, thermal properties of CER were averaged to get the figure of merit for thermal diffusivity as (44.2 +/- 3.6) x 10(-3) cm(2)/s, for thermal conductivity (228 +/- 32) mW/cm K, the thermal effusivity (1.09 +/- 0.06) W s(0.5)/cm(2) K and volume heat capacity (5.2 +/- 0.7) J/cm(3) K, which are in excellent agreement with results of a disk prepared from commercial MTA-Angelus (grain size < 10 mu m using 57 mu l of distilled water). (C) 2013 AIP Publishing LLC.